Monetary policy surprises and the expectations hyothesis at the short of the yield curve - Selva Demiralp (TÜSİAD-Koç University Economic Research Forum, 2008)
We test the expectations hypothesis by analyzing changes in three month T-Bill rates (TB3) after FOMC meetings. By estimating the revisions in expectations of future overnight rates, we find a one-to-one relationship between changes in TB3 and path revisions.
Keywords: E43; 330; Expectations Hypothesis; Policy Path Revisions; Geldpolitik; Erwartungstheorie; Zinsstrukturtheorie; Schatzpapier; Schätzung; Theorie; USA